2021
DOI: 10.1016/j.isci.2020.101959
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic structural property of organic-inorganic metal halide perovskite

Abstract: Unique organic-inorganic hybrid semiconducting materials have made a remarkable breakthrough in new class of photovoltaics (PVs). Organic-inorganic metal (Pb and/or Sn) halides (-I, -Br, and -Cl) are the semiconducting absorber with the crystal structure of the famous ''Perovskite''. It is widely called ''perovskite solar cells (PSCs)'' in PV society. Now, the power conversion efficiency (PCE) of PSCs is recorded in 25.5%. Prototypical composition of the absorbers is (A = methylammonium [MA], formamidinium [F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 97 publications
1
28
0
Order By: Relevance
“…Rietveld refinements of the experimental XRD patterns are in agreement with the existence of orthorhombic (Pnma), tetragonal (I4/mcm) and cubic (Pm3m) phases for both the compounds. 18,19,29 The temperature variations of obtained lattice patameters for MAPbI 3 and MAPbBr 3 are plotted in Figure 1c,d, respectively. Refined unit cell parameters (red color in Figure 1c,d) of MAPbI 3 and MAPbBr 3 in orthorhombic phase are consistent with the previous reports with negative thermal expansion coefficient for "a" and positive thermal expansion coefficient for both "b" and "c", whereas total volume expansion is positive (not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rietveld refinements of the experimental XRD patterns are in agreement with the existence of orthorhombic (Pnma), tetragonal (I4/mcm) and cubic (Pm3m) phases for both the compounds. 18,19,29 The temperature variations of obtained lattice patameters for MAPbI 3 and MAPbBr 3 are plotted in Figure 1c,d, respectively. Refined unit cell parameters (red color in Figure 1c,d) of MAPbI 3 and MAPbBr 3 in orthorhombic phase are consistent with the previous reports with negative thermal expansion coefficient for "a" and positive thermal expansion coefficient for both "b" and "c", whereas total volume expansion is positive (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Crystal structure of hybrid lead halide perovskite involves a positively charged organic unit, methylammonium ion (MA + ), with a permanent dipole, located at the center of a lead halide cage. 17,18 These hybrid lead halide perovskites crystallize in orthorhombic phase at low temperature and have high/roomtemperature cubic perovskite phase depending on the halide ion with an intermediate tetragonal phase. 19 Further, it is also observed that the MA + dipoles order in an antiferroelectric arrangement in low-temperature orthorhombic phase; however, the behavior of this MA + dipole and its role in determining the physical and chemical properties in high temperature tetragonal and cubic phase are still developing.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting material is physically soft and dynamic in nature, [10][11][12][13] significantly affecting its optoelectronic performance and long-term stability.…”
Section: Graphical Toc Entry Manuscriptmentioning
confidence: 99%
“…Yet, the interpretation of experimental results argues both ferroelectricity and non‐ferroelectricity in CH 3 NH 3 PbI 3 perovskite. [ 3–63 ] This controversy is related to the polarization‐electric hysteresis, the nanoscale domain structure, etc. Consequently, there are also disagreements on the effect of ferroelectricity on photovoltaic action in MHPs, both detrimental effect (e.g., current‐voltage hysteresis) and beneficial effect (e.g., facilitating photogenerated charge carrier dissociation and transport).…”
Section: Introductionmentioning
confidence: 99%